Impact of the director`s circular no 36 of 2006 on the assessment and evaluation of teaching and learning in accounts at Ordinary Level in Mbare Secondary Schools - Manenji, Barbra (Midlands State University, 2017)
The study focused on assessing the effectiveness of the Director’s Circular No P36 of 2006 in the teaching and learning of Accounting at Ordinary level in Harare Province of Zimbabwe. The study came about after realising the Circular P36 of 2006 which was adopted as the lone evaluation and assessment tool for teachers. The study, therefore, aimed at assessing teachers’ perceptions on the use of Circular P36 of 2006 in the assessment and evaluation as well as to evaluate the challenges faced by teachers in implementing the policy, assess its impact and lastly, find out strategies to mitigate challenges faced by teachers in implementing the Circular P36 of 2006. The study was conducted in a qualitative approach using a case study design in which four secondary schools were randomly selected in cluster 14 Mbare/Hatifield District in Harare Province. The study targeted all the Accounts Ordinary level classes but since the study was more concerned with the assessment and evaluation of teachers in the teaching and learning the study sample comprised of the eight (8) Accounts teachers and four (4) Heads of Departments purposively selected from the four schools respectively. Data was generated mainly through questionnaires self-administered to the eight Accounts teachers and face to face interviews with four Heads of the Accounts Departments in the study. The study found out that teachers were not confident in the education policy P36 of 2006 and perceived the policy as inadequate as a standalone assessment and evaluation tool although the policy has a fairly equal opportunity to enhance teachers’ performance in the teaching and learning of Accounting. Major challenges noted in implementing the policy were overloads; compromised on teacher-pupil individual attention; the nature of the Accounting topics learnt at O’ level; nature of the Accounting exercises; inadequate time allocation and shortages of Accounting learning support materials. Lastly, the educational policy was noted as being incompatible with other teaching approaches such as collaborative/pupil-centered, hence, the study recommends that there is a need to revisit the educational policy in line with current teacher-pupil ratios and the textbooks being used in schools. There is also need to reconsider time allocation for the lesson or periods per week, make the policy explicit on expectations, time allocations per lesson and periods per work.